Comparison of Traditional Chinese Medicine in the Long-Term Secondary Prevention for Patients with Ischemic Stroke: A Systematical Analysis - Li, Jiali; Zhao, Xixi; Zhang, Yangyang; Wan, Haitong; He, Yu; Li, Xiaohong; Yu, Li; Jin, Weifeng (Frontiers in Pharmacology, 2021)
Background: Keeping in view the high recurrence rate and risk of ischemic stroke, combinatorial therapy involving traditional Chinese medicine (TCM) with conventional Western medicine (WM) is receiving wider scientific attention. Thus, a systematical analysis was made to explore the efficacy of TCM+WM in the long-term secondary prevention for patients with ischemic stroke. Methods: Qualified inclusion and exclusion criteria were set up beforehand, and two researchers independently read the articles, extracted data, and evaluated the quality of included articles according to Cochrane Reviewer’s Handbook 5.1 method. For the sake of comprehensive data acquisition, seven databases from the time of their establishment to May 5, 2021, have been searched completely. Additionally, pairwise meta-analysis was made to compare TCM+WM vs. WM, and network meta-analysis was conducted by frequentist random effects models for the comparison of different kinds of TCM+WM via indirect evidence. The primary outcomes defined were recurrent stroke and NIHSS. Secondary outcomes were fibrinogen (Fib) fasting blood glucose (FBG), triglycerides (TG), and total cholesterol (TC). Safety outcomes were outlined as all-cause mortality and adverse events (AEs). Furthermore, Stata16.0 software was used to accomplish the systematical analysis and cluster analysis. Results: In total, 47 qualified randomized controlled trials (RCTs) including 10,732 patients were taken into consideration. Seven traditional Chinese medicines included in the study are Naoxintong capsule (NXT), Tongxinluo capsule (TXL), Buyang Huanwu decoction (BYHW), Naomaitai capsule (NMT), Dengzhan Shengmai capsule (DZSM), Naoshuantong capsule (NST), and Maixuekang capsule (MXK). With respect to their primary outcomes, all kinds of TCM+WM were significantly more effective than WM (e.g., NXT in recurrent stroke (OR=0.54, P<0.01), TXL in NIHSS (WM=−1.4, P<0.01)). Additionally, the outcomes of cluster analysis indicated that MXK+WM and NST+WM had relatively good preventive effects for recurrent stroke, NIHSS, and all-cause mortality. There was no significant difference in the comparisons of AEs; however, this may arise from the lack of sufficient data. Conclusion: According to our systematical analysis, MXK+WM and NST+WM had relatively good secondary prevention effects for patients with ischemic stroke regarding recurrent stroke, NIHSS, and all-cause mortality. Nevertheless, better, high-quality, large-sample randomized clinical trials (RCTs) are required to verify our conclusions in the future. Systematic Review Registration: [https://inplasy.com/inplasy-2021-5-0036/], identifier [INPLASY202150036].